Problems of obstacles to sexual impotence and so-called "gender change" in the context of the KEP General Decree of November 26, 2019 - Stawniak, Henryk (Prawo Kanoniczne, 2021)
The study is an attempt to approximate important elements of the obstacle to sexual impotence and problems of so-called "gender change" in the perspective of the desire to marry. Moreover, the article wants to show what is the real novelty in terms of these two issues, especially in the light of deceptive media information, and present some solutions of the General Decree on talks between a priest and fiancees, not excluding the relevant criticism